Microstructure evolution and grain refinement mechanism of 316LN steel - Zhang, Li; Ren, Jie; Zheng, Zhichao; Guan, Lanfang; Liu, Chengzhi; Liu, Yanlian; Cheng, Shengwei; Su, Zexing; Yang, Fei (High temperature materials and processes, 2024)
The hot compression behavior of 316LN stainless steel for the supporting system in a magnet confinement fusion reactor was isothermally compressed at 1,050℃ and 0.1 s . Electron backscatter diffraction was used to study the microstructure and texture evolution during the deformation process. The results showed that the necklace structure is eventually formed by increasing compression strain due to dynamic recrystallization (DRX). The proportion of low-angle grain boundaries first increases and then decreases. The dominant DRX mechanism of 316LN is discontinuous DRX, which is characterized by the grain boundary bulging. Besides, twinning is found to be induced to accommodate the plastic strain, helping the development of DRX.